Appropriating Grammar as a Tool in Writing Activities: Student's Perception - Elya Kristian Fernando; Maman Suryaman (Journal of English Language and Education, 2022)
This study explores the motivations and perspectives of 2 university students in Indonesia. In this research, author employed qualitative design with the research method "Interview Study". The author collects data using Semi-structured Interviews, meanwhile, the author uses Thematic Analysis by Braun and Clarke for data analysis. It was found that the use of Grammarly independently by the participants was motivated by feedback from the teacher, belief in learning, feedback preference and English proficiency. In addition, their abilities also shape their perspective on the features provided by Grammarly. Students’ AWE appropriation is influenced by their belief about learning, preference on feedback and language proficiency